(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1998)
The existence of one of the original specimens of Ctenognathichthys bellottii (De Alessandri 1910), figured and labelled as ‘type specimen’ by De Alessandri himself, raises a nomenclatural question as there is also a neotype designated by Bürgin (1992). The International Commission of Zoological Nomenclature has been asked to rule on the validity of the neotype. As some of the requirements for the designation of a neotype were not met, the holotype should be treated as the name-bearing type. The discovery of this species in both the Besano Formation (Grenzbitumenzone Auct.) and the Perledo-Varenna Formation is very important from a stratigraphic point of view, confirming that the so called Perledo fish-fauna is composed of different assemblages. In fact, the Perledo fauna has most species in common with the Ca’ del Frate (Viggiù, Varese, Italy) fauna from the Kalkschieferzone (uppermost Meride Limestone), which is latest Ladinian in age, while a few of the Perledo species have been found also in the Grenzbitumenzone and/or in the lower Meride Limestone of Lower Ladinian age.